Atomic layer deposition of TiO2 thin films on electrospun poly (butylene adipate-co-terephthalate) fibers: Freestanding TiO2 nanostructures via polymer carbonization. (2019) - Rodrigues, Bruno V.M.; Dias, Vanessa M.; Fraga, Mariana A.; da Silva Sobrinho, Argemiro S.; Lobo, Anderson O.; Maciel, Homero S.; Pessoa, Rodrigo S.
Abstract: Herein, freestanding TiO2 nanostructures were successfully prepared by atomic layer deposition (ALD) using electrospun poly (butylene adipate-co-terephthalate) (PBAT) fibers as templates. Initially, ultrathin PBAT fibers were produced by electrospinning. Afterwards, TiO2 thin film was deposited onto the fibers by using an ALD reactor operating in thermal mode at 100 °C and 150 °C. A thermogravimetric furnace was used to promote the carbonization of the polymeric core. XRD analysis revealed the growth of amorphous TiO2 thin films onto the polymeric substrate; after carbonization, the anatase phase was dominant over to rutile. FE-SEM micrographs showed the generation of nanostructured TiO2 tubes with different diameters, but with controlled wall thickness. While conducting the ALD process at 100 °C led to crystalline grains of TiO2 nanotubes, increasing to 150 °C seemed to have a negative effect, since the crystalline grains were no longer evident. This study has demonstrated the feasibility of producing TiO2 nanostructures, which may find a wide range of applications, such as in photocatalysis and biomedical devices.